The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.22159/ajpcr.2018.v11i11.24889
|View full text |Cite
|
Sign up to set email alerts
|

Ecuadorian Quinoa (Chenopodium Quinoa Willd) Fatty Acids Profile

Abstract: Objective: The aim of this study was to determine the methyl esters fatty acids (FAMEs) profile of quinoa seeds (Chenopodium quinoa Willd) of a sample cultivated in Guaranda, Ecuador.Methods: Quinoa oil was obtained from quinoa seeds using the Soxhlet method. FAMEs identification and quantification were carried out using the gas chromatography (GC) with a mass spectrometry (MS), using the database Library NIST14.L to identify the fatty acids present in quinoa oil.Results: Quinoa oil from Ecuador was analyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
(17 reference statements)
0
1
1
Order By: Relevance
“…The present study showed that both varieties are rich in linoleic acid but only hualhuas contains appreciable amounts of linolenic acid (8.981%), while the variety quinoa 1 only contained a very low percentage (1.261). The fatty acid profiles of quinoa varieties in the current study somehow fall within the ranges of fatty acids reported by Altuna et al (2018) andRepo-Carrasco et al (2003) with only a higher value for linolenic in the hualhuas variety. The unsaturated fatty acids in quinoa in the present study are extremely high, nearly 7-8 times the saturated fatty acids.…”
Section: Discussionsupporting
confidence: 85%
“…The present study showed that both varieties are rich in linoleic acid but only hualhuas contains appreciable amounts of linolenic acid (8.981%), while the variety quinoa 1 only contained a very low percentage (1.261). The fatty acid profiles of quinoa varieties in the current study somehow fall within the ranges of fatty acids reported by Altuna et al (2018) andRepo-Carrasco et al (2003) with only a higher value for linolenic in the hualhuas variety. The unsaturated fatty acids in quinoa in the present study are extremely high, nearly 7-8 times the saturated fatty acids.…”
Section: Discussionsupporting
confidence: 85%
“…Multiple correlation analysis in our experiment showed no principal difference between the FA content of quinoa seeds and the salinity chemistry ( Figure 2B). The value of OA pattern in quinoa seeds was 22.8 ± 29.5%, which is higher than described early by other authors (Altuna et al, 2018). Interestingly, the values of LA from the control were found to be higher than those reported in literature (48.1 ± 52.3%, respectively).…”
Section: Discussioncontrasting
confidence: 63%
“…Farmers and agribusiness enterprises that consider only grain production without the application of transformation technologies downgrade the commercial value of quinoa [21]. Several public and private institutions, universities, and research centers in Ecuador are currently developing improved varieties, including thoroughly characterizing the physico-chemical and nutritional traits, protein and amino acid contents, fatty acids, vitamins and minerals, phytohormones, antioxidants, phytosterols, and dietary fiber, as well as the identification and use of saponins [70][71][72][73]. Additionally, applications of thermal processes and bioprocesses have been studied in order to increase mineral bioavailability, the level of acceptability, and the nutraceutical value of quinoa grain [74].…”
Section: Quinoa Transformationmentioning
confidence: 99%